MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN IPS SDN MELALUI PENGGUNAAN MEDIA GAMBAR SISWA KELAS IV SDN 001 PEMATANG KECAMATAN BATANG PERANAP (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2015)
action research has been conducted to determine the increase in social studieslearning outcomes with the use of media images in grade IV SDN 001 Pematang Batang PeranapDistrict of the Academic Year 2013/2014. This study was conducted in January 2013. The subjectswere students of class IV with the number of students of 30 people consisting of 12 male studentsand 18 female students. The parameters measured were the result of learning that consists ofabsorption, completeness student learning, student activities and teacher activity seen from thelearning outcomes of each cycle. Data were analyzed descriptively. The results showed thatincreased student learning outcomes, can be seen from the absorption students first cycle withan average of 76.83 daily tests (both categories) increased cycled II with an average of 81.16daily tests (both categories). Mastery learning students who complete the first cycle of individual27 people (90.00%) with excellent category increased in the second cycle is the complete individual28 people (93.33%) with excellent category. Student learning activity also increased, judgingfrom the average percentage of student activity.In the first cycle average of 73.34% of student activity (enough category) increased in the secondcycle the average activity of the students became 85.83% (excellent category) .Aktivitas teacherin the learning process has been good and has increased an average of percentage of teachers inthe first cycle activities 84.29% (both categories) increased in the second cycle the averageactivity of the teacher to 100.00% (excellent category). From these results it can be concludedthat the use of media images can improve learning outcomes fourth grade social studies studentsof SDN 001 Pematang Peranap Indragiri Hulu District of the Academic Year 2013/2014.Keywords: Results Learning, Media Image